EVALUASI PENGARUH KOLEKTIBILITAS KREDIT TERHADAP PROFITABILITAS BANK (PT Bank Rakyat Indonesia (Persero), Tbk. Periode 2008 - 2010) - , EFFENDI WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted to evaluate the effect of loan collectibility classified as current, special mention (DPK), substandard, doubtful, and bad to the bank profitability that is proxied by Net Interest Margin (NIM). The data in this research obtained by quoting Monthly Published Financial Statements of Bank Indonesia at PT Bank Rakyat Indonesia (Persero) Tbk. from 2008 to 2010. The research method used in this research is multiple linear regression, by testing hypotheses using t-statistics to test coefficients of partial regression and also f-statistics to test the significance of influence collectively with a significance level of 5%. Furthermore, a test on the classic assumption which includes normality test, multicolinearity test, heteroscedastisity test and autocorrelation test was also performed. During the observation period indicates that the data research was normally distributed. Based on multicolinearity test and heteroscedasticity test, variable digressing of classic assumption was not found. Based on autocorrelation test,variable digressing of assumption was found, but after the improvement of data showed that there was no disgressing of autocorrelation, it indicates that the available data are qualified to use multiple linear regression model. Based on the results of the analysis indicate that current collectibility data has a positive and significant effect on profitability, while collectibility in a particular attention (DPK) has a negative and insignificant effect on profitability, substandard collectibility has a positive and insignificant effect, for doubtful and bad collectibility, both have a negative and significant effect on profitability. This research can be used as a planning and management considerations in managing the bank's earning assets to achieve optimal levels of profitability.